Variable deposit betas and bank exposure to interest rate risk - Emin, Mustafa; James, Christopher; Li, Tao (Journal of Financial Intermediation, 2025)
Following the global financial crisis, banks lengthened the average maturity of their assets relative to that of their liabilities, principally by increasing their investments in mortgage-related assets. Whether such maturity transformation exposes banks to interest rate risk depends, in part, on the effectiveness of bank deposits as a hedge against interest rate shocks. In this paper we provide evidence that interest pass-through rates on deposits vary significantly with interest rates, which reduces the effectiveness of deposits as a hedge when interest rates increase. The dynamic nature of the deposit betas explains, in part, why the duration of bank equity varies with interest rates and why interest rate risk models need to account for how pass-through rates vary with interest rates.